Pengaruh Pelatihan SDM Terhadap Kebertahanan Masyarakat Desa Wisata Pulesari Pada Masa Pandemi COVID-19 - Fathiyyah Nur Andina; Nissa Larasati (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2022)
The spread of the COVID-19 virus that has spread throughout the world has had a tremendous impact, one of which is for the tourism sector. Many tourist destinations have had to close during the pandemic. Pulesari Tourism Village implements community based tourism, where every year the community is given HR training so that they can continue to improve the development of the quality of their tourism. However, during the pandemic, Pulesari Tourism Village did not operate so it did not generate economic income from tourists. This study aims to understand the implementation of HR training that the Pulesari Tourism Village community has participated in before the pandemic and its implications for the community's economic resilience during the COVID-19 pandemic. The research method was obtained from in-depth interviews conducted by purposive sampling. The study found that the form of community training, namely training on creative business development and digital marketing, had implications for the economic resilience of the Pulesari Tourism Village community during the COVID-19 pandemic.